"Que bom, que bom, ai que bom!": da existência da relação retórica de interjeição - Geovane Fernandes Caixeta (2015)
In this study we focused on interjections in Brazilian Portuguese from a functionalist perspective. In doing so, we took interjections from the periphery of linguistic studies and considered them as a language phenomenon. At the time a speaker uses interjections, he or she vividly conveys his or her emotions, showing involvement either with the socio-communicative event, his or her interlocutor, the subject, himself or herself, or all of these elements. In face of that, our goal was to investigate interjectional occurrences in texts aiming specially at identifying the conditions and / or semantic-pragmatic restrictions so as to recognize a text span in interjectional occurrences able to contribute to the existence of a rhetorical relation in the field of emotions, what we referred to as interjection rhetorical relation. With this purpose, we presented a set of considerations on graphophonemic, grammatical, semantic and pragmatic treatment of interjectional occurrences. In the theoretical background, we briefly described the principles of Functionalism and some conceptual notions necessary to analyze interjectional occurrences. Also, we addressed Rhetorical Structure Theory (RST), which is our theoretical and methodological framework. Next, we described the corpus and the methodology. Once interjections are considered both an oral and written language phenomenon, the corpus was unsystematically composed by reader letters, poems, novels, opinion pieces and journalistic chronicles. With regard to the methodology, we designed a framework in order to operationalize our analysis. Such framework was based on a) RST so as to establish a rhetorical relation and b) theoretical notions as components of the speaker's current mental state, complex judgment and performatization. The interjectional utterance, which is a text span formed by an interjectional occurrence in the satellite function of a nucleus-satellite-like rhetorical relation, was the unit of analysis underpinning that framework. Then, we analyzed interjectional occurrences in order to find plausible arguments for the definition of interjection rhetorical relation. Finally, we analyzed interjectional occurrences by means of the operational framework so as to establish conditions and / or restrictions concerning the existence of an interjection rhetorical relation. Owing to the diversity of behavior concerning interjectional occurrences found in the corpus, they were grouped into emotional, volitional, cognitive, persuasive and formulaic. This grouping signals the existence of subtypes of interjection rhetorical relation, which was confirmed. We concluded that interjections are totally or partially vividly expressed occurrences, with greater or lesser involvement of the speaker, able to establish rhetorical relations in the field of emotions. Thus, these rhetorical relations not only contribute to the consistency between text spans at a macro structural level; but also color expressively, emotionally, and emotively communicative exchanges; and particularize the speaker as a subject of intentions and/or evaluative attitudes both in the production and reception of texts. Given these results, we suggest that interjection rhetorical relation be added to the RST rhetorical relations. Our study showed that interjectional occurrences convey poeticity due to their capacity of emotional and emotive encapsulation, which is remarkably expressive. The interjectional speaker is, therefore, poetic.